Perbandingan Efektivitas Platelet Rich Plasma VS Hypertonic Dextrose Prolotherapy terhadap Perbaikan Klinis Pasien Osteoartritis Genu - POERWANTO, EKA; HENDRATA ERRY ANDISARI2; Rr. MUTIARA DEVANIA SAMARA QALBA; RONALD PRATAMA ADIWINOTO (Universitas Hang Tuah, 2024)
ABSTRACT Background: Knee osteoarthritis (OA) affects mainly older individuals, causing joint degeneration and decreased mobility. While current treatments include medications and surgery, regenerative therapies like Platelet Rich Plasma (PRP) and Hypertonic Dextrose Prolotherapy (HDP) offer promising alternatives. This study aims to compare the effectiveness of PRP and HDP injections in knee OA patients, providing insights into optimal treatment choices. Methods: This experimental analytical study involved two groups of participants. Group 1 (N=20) received PRP injections three times into both knees with four-week intervals. Group 2 (N=20) received HDP injections with 20% concentration into both knees with the same intervals. Numeric Rating Scale (NRS) and Western Ontario and McMaster University Arthritis Index (WOMAC) scores were assessed before and after injections to evaluate changes in pain, stiffness, and functional limitation. Results: Both PRP and HDP injections significantly reduced NRS scores, pain, stiffness, functional limitation, and total WOMAC scores. The reduction in pain, functional limitation, and total WOMAC scores was higher with HDP, while PRP was more effective in reducing stiffness. Mild pain during injection and knee swelling were reported by some participants, but no systemic complaints were noted, and all side effects resolved within a week. Conclusion: Both PRP and HDP injections are equally effective in reducing pain and stiffness and improving function in knee OA patients. These procedures offer promising, cost-effective, and easily administered therapies for knee OA, with HDP being a more cost-efficient option compared to PRP. Keywords: Osteoarthritis, regenerative therapy, comparison